KERJA SAMA BADAN SIBER DAN SANDI NEGARA (BSSN) INDONESIA DENGAN DEPARTMENT OF FOREIGN AFFAIRS AND TRADE (DFAT) AUSTRALIA DALAM PENGEMBANGAN CYBER SECURITY - Dhiyanka Magrisa; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The development of technology has gradually permeated all aspects of modern human life. One of them is the ease of getting information and communication. Unlimited internet access creates new threats, namely cyber threats. Various countries are trying to improve their cybersecurity, including Indonesia by working with Australia. In its implementation, this cooperation is represented by the National Cyber and Crypto Agency (BSSN) from Indonesia and the Department of Foreign Affairs and Trade (DFAT) from Australia. This research describes the forms of cooperation between the National Cyber and Crypto Agency (BSSN) with the Department of Foreign Affairs and Trade (DFAT) in the development of cyber security.This research uses descriptive qualitative research methods. The perspective used in this research is neorealism, and uses the theory of international cooperation with the form of bilateral cooperation. Bilateral cooperation is a situation that illustrates the mutual and influencing relationship between the two countries and arises as a result of the commitment between the two countries.The results of this research describe the forms of cooperation that exist between the National Cyber and Crypto Agency (BSSN) and the Department of Foreign Affairs and Trade (DFAT) which is based on the MoU between the two countries in the cybersecurity sector in 2018. There are several forms, namely; Cyber Boot Camp, ASPI (Australian Strategic Policy Institute) Cyber Policy Workshop, Cyber Business Connection: Austrade and AustCyber in the digital economy, and Cyber Policy Dialogue. Keywords: National Cyber and Crypto Agency (BSSN), Department of Foreign Affairs and Trade (DFAT), International Cooperation, Cybersecurity.